Le Topkapı Kültür Parkı : fabriquer un parc public à Istanbul - Helin Karaman (European Journal of Turkish Studies)
This paper analyses how public parks are manufactured in Istanbul in the case of Topkapı Kültür Parkı, located in the district of Zeytinburnu. Based on direct observations and interviews carried out with municipal authorities and the park’s caretakers, this study argues that municipal authorities manufacture the park through the confiscation of land, the redefinition of urban life, and the promotion of the values of the Justice and Development Party [Adalet ve Kalkınma Partisi, AKP]. Firstly, the history of the place prior to its urban transformation will be studied with a particular focus on the issues raised by the eviction of undesirables and the erasure of alternative memories and previous uses of the land. The paper will move on to discuss the development of Topkapı Kültür Parkı in the 2000s as correlative to the public park model established in Istanbul since the 1990s and the question of the standarisation of urban space. Finally, this paper focuses on the ways in which the forms, uses and regulation of urban public spaces are connected and how behavioural norms are manufactured.